Campath-1 Abs 'in the bag' for hematological malignancies: the Cape Town experience. - Novitzky, N; Thomas, V; Hale, G; Waldmann, H (2004)
BACKGROUND: We examined the strategy of T-cell depletion of HLA-identical sibling grafts for the prevention of GvHD, as well as disease control and overall survival. PATIENTS AND METHODS: The myeloablative conditioning was radiation based. The source of stem cells was BM in 62, and cytokine-mobilized PBPC in 68 patients. GvHD prophylaxis was by ex vivo incubation of the stem-cell concentrates with Campath-1G (anti-CD52; n=76) or Campath-1H (n=54). RESULTS: Patients receiving PBPC grafts were older (median 38.5) than those undergoing BMT (median 31; P=0.002). More patients in the PBPC group developed chronic GvHD (p<0.01). While no post-transplant GvHD prophylaxis was given to BMT recipients, prednisone 30 mg daily was prescribed to 12 and CYA for 90 days to a further 32 patients who had received PBPC grafts. Median follow-up was 1055 (range 28-4867) days. Although there was no difference in the survival between patients who received BMT or PBPC, death was from disease recurrence in 16 and nine (p=0.03; chi(2) test) subjects, respectively. Multivariate analysis showed that outcome was particularly favorable in those who were given<20 mg Campath-1 (survival: 28/39 versus 12/29; P=0.01), and in the subgroup of 30 patients who received Campath-1H and post-transplantation CYA. DISCUSSION: In patients receiving BMT, Campath-1 Abs effectively prevent GvHD. For those treated with PBPC grafts, the combination of T-cell depletion and post-transplantation CYA is equally effective, without an obvious increase in disease recurrence.